2011
DOI: 10.1097/ccm.0b013e31822629ba
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical cord blood mesenchymal stem cells protect mice brain after trauma*

Abstract: These findings indicate that human umbilical cord blood mesenchymal stem cells stimulate the injured brain and evoke trophic events, microglia/macrophage phenotypical switch, and glial scar inhibitory effects that remodel the brain and lead to significant improvement of neurologic outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
113
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(119 citation statements)
references
References 50 publications
5
113
0
1
Order By: Relevance
“…As previously reported for HUCB-derived MSCs 25 and MNCs, 23 in this study, HUCB-derived MNCs and CD45 + cells intravenously administered one day post-trauma rapidly home (within 1.5-2 h; Fig.6D and Fig. 7) to the brain lesion site.…”
Section: Cd45 1 Cells Neurotherapy In Brain Injurysupporting
confidence: 57%
See 2 more Smart Citations
“…As previously reported for HUCB-derived MSCs 25 and MNCs, 23 in this study, HUCB-derived MNCs and CD45 + cells intravenously administered one day post-trauma rapidly home (within 1.5-2 h; Fig.6D and Fig. 7) to the brain lesion site.…”
Section: Cd45 1 Cells Neurotherapy In Brain Injurysupporting
confidence: 57%
“…HUCB-derived MSCs also were found to stimulate the injured brain of TBI mice, evoking trophic events and the phenotypic switch of microglia/ macrophages, inhibiting glial scarring and leading to significant improvement of neurological outcomes. 25 Currently, a variety of MSCs, 8 including HUCB-derived MSCs, 24,25 represent the most active stem cell population used for pre-clinical and clinical trials of brain injury. While the majority of these regenerative clinical trials using MSCs have proved safety, phase II clinical trials are still ongoing and are facing issues of efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…UC-MSCs also provide a pool of varying kinds of growth factors, including matrix metalloproteinase-2, matrix metalloproteinase-9, hepatocyte growth factor, transforming growth factor β1, granulocyte-colony stimulating factor, fibroblast growth factor 2 and interleukin-6 (Santos et al, 2015). Based on these mechanisms, Zanier et al have suggested that UC-MSCs can protect the murine brain after trauma (Zanier et al, 2011) and impact traumatic brain injury in humans (Wang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, extracellular components of the glial scar that persists adjacent to the injury site have been found to inhibit neurite extension (e.g., neurocan, Nogo protein), thus limiting regeneration (for review, see Properzi et al, 2003). Transplantation of MSCs helps overcome this glial scar limitation following experimental stroke Li et al, 2005;Pavlichenko et al, 2008;Shen et al, 2008) and TBI (Zanier et al, 2011). Following ischemic stroke, rats treated with rat MSCs transplanted intravenously had decreased glial scar thickness at both the acute (3 and 6 days post-stroke; Pavlichenko et al, 2008) and chronic (4 months post-stroke; Li et al, 2005) phases.…”
Section: Neuroregenerationmentioning
confidence: 99%